Невероятные приключения кота Сократа - Самарский Михаил Александрович (Мастер ГранПри, 2018)
Экземпляры: БС (20230907) / Инвентарный номер: ФЖД11916 / Сис.шифр: 84(2) / Авт.знак: С 17 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4